MAGNITUDE DRIFT EFFECT WINNER AND LOSER STOCKS: LQ45 AND FTSE100 - Felita Tanuprasodjo; Putu Anom Mahadwartha (Journal of Management and Business, 2016)
This research is aimed to examine and find out empirical evidence of magnitude drift effect on 10 winner LQ45, 10 loser LQ45, 5 winner FTSE100 Malaysia and 5 loser FTSE100 Malaysia. One sample t-test and independent sample t-test are used to test the magnitude drift effect. The result show the positive magnitude drift effect on Monday-Wednesday at 10 Winner LQ45 and 5 winner FTSE100, Monday-Tuesday at 10 Loser LQ45, Monday-Thursday at 5 Loser FTSE100 and the negative magnitude drift effect occurs on  Thursday-Friday at 10 Winner LQ45 and 5 Loser FTSE100, Wednesday-Friday at 10 Loser LQ45 and Friday-Monday at 5 Winner FTSE100. Magnitude drift in Malaysia occurs more than magnitude drift  in Indonesia.